Student profiling on university co-curricular activities using cluster analysis - Rajenthran, Hemabegai; Mohd Shaharanee, Izwan Nizal; Jamil, Jastini (IP Publishing LLC, 2017)
In higher learning institutions, the co-curricular programs are needed for the graduation besides the standard academic programs.By actively participating in co-curricular, students can attain many of soft skills and proficiencies besides learning and adopting campus environment, community and traditions.Co-curricular activities are implemented by universities mainly for the refinement of the academic achievement along with the social development.This studies aimed to analyse the academic profile of the co-curricular students among uniform units. The main objective of study is to develop a profile of student co-curricular activities in uniform units. Additionally, several variables has been selected to serve as the characteristics for student co-curricular profile.The findings of this study demonstrate the practicality of clustering technique to investigate student’s profiles and allow for a better understanding of student’s behavior and co-curriculum activities.